Food in zones of conflict: cross-disciplinary perspectives - Collinson, Paul; Macbeth, Helen M.; Shepler, Susan; Oyeniyi, Bukola Adeyemi; Talton, Benjamin; Messer, Ellen; Strauss, Michael J.; Akinyoade, Akinyinka; Cwiertka, Katarzyna J. (The anthropology of food and nutrition, 2014)
Introduction / Paul Collinson and Helen Macbeth 1. - Chapter 1. ‘Try to imagine, we didn't even have salt to cook with.’: Food and War in Sierra Leone / Susan Shepler 27. - Chapter 2. Landmines, Cluster Bombs and Food Insecurity in Africa / Bukola Adeyemi Oyeniyi and Akinyinka Akinyoade 39. - Chapter 3. Special Nutritional Needs in Refugee Camps: A Cross-disciplinary Approach / Jeya Henry and Helen Macbeth 53. - Chapter 4. Patterns of Household Food Consumption in Conflict Affected Households in Trincomalee, Sri Lanka / Rebecca Kent 65. - Chapter 5. Engaging Religion in the Quest for Sustainable Food Security in Zones of Conflict in Sub-Saharan Africa / Lucy Kimaro 77. - Chapter 6. Livestock Production in Zones of Conflict in the Northern Border of Mexico / Daria Deraga 85. - Chapter 7. The Logic of War and Wartime Meals / Nives Rittig Beljak and Bruno Beljak 95. - Chapter 8. Nutrition, Food Rationing and Home Production in U.K. in the Second World War / Helen Lightowler and Helen Macbeth 107. - Chapter 9. Beyond the Ration: Alternatives to the Ration for British Soldiers on the Western Front 1914-1918 / Rachel Duffett 123. - Chapter 10. Sustaining and Comforting the Troops in the Pacific War / Katarzyna J. Cwiertka 133. - Chapter 11. Enemy Cuisine: Claiming Agency, Seeking Humanity and Renegotiating Identity through Consumption / K. Felicia Campbell 145. - Chapter 12. The Memory of Food Problems at the end of the First World War in Subsequent Propaganda Posters in Germany / Tania Rusca 155. - Chapter 13. Echoes of Catastrophe: Famine, Conflict and Reconciliation in the Irish Borderlands / Paul Collinson 171. - Chapter 14. ‘Land to the Tiller’: Hunger and the End of Monarchy in Ethiopia / Benjamin Talton 185. - Chapter 15. Prospects for Conflict to Spread through Bilateral Land Arrangements for Food Security / Michael J. Strauss 197. - Chapter 16. Food, Conflict and Human Rights: Accounting for Structural Violence / Ellen Messer 209